Preparation method and application of aramid nanofiber aerogel formed with assistance of polyvinyl alcohol
By introducing polyvinyl alcohol into the aramid nanofiber aqueous dispersion, the problems of long preparation cycle and difficulty in dispersion of aramid nanofiber-based aerogels are solved, and the preparation of strong and multifunctional aerogels is realized, and the carbonization of high temperature is achieved. Derivatives are used in microwave absorbing materials, improving performance and application range.
Patent Information
- Application Number
- CN202411293383.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems in the preparation of aramid nanofiber-based aerogels with long preparation cycles, low yields, and large amounts of organic solvents and strong alkalis. It is difficult to meet the needs of large-scale green preparation, and the aramid nano obtained by mechanical cracking method. It is difficult to disperse the fibers in water and are difficult to directly process into an aerogel.
By introducing polyvinyl alcohol into the aramid nanofiber aqueous dispersion, the fibers are fixed by using its long chain interspersion and hydrogen bonds between the molecular chains and the fiber surface, a complete aerogel after freeze-drying is achieved, and polyethylene is reduced by heat treatment The adhesion of alcohol is obtained to obtain an aerogel with tensile resilience.
It has realized the construction of a tough and multifunctional aramid nanofiber aerogel in a green water system, which has torsion, bending and cutting properties, and is used in microwave absorption materials through high-temperature carbonized derivatives, improving the performance and application of the material. scope.
Smart Images

Figure CN119286043A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel preparation, and specifically relates to a polyvinyl alcohol-assisted aramid nanofiber aerogel and a preparation method thereof, as well as application of a high-temperature carbonized derivative thereof in microwave absorbing materials. Background Art
[0002] Aerogel is a material with a nanoscale porous network structure. It is widely used in thermal insulation and sound absorption, adsorption catalysis, hydrogen storage and energy storage due to its high specific surface area, high porosity, low bulk density and low thermal conductivity. Aramid nanofibers have excellent intrinsic properties such as high temperature resistance, acid and alkali resistance, high strength and high modulus. Its high aspect ratio and high specific surface area at the nanoscale make it an ideal material for preparing high-performance aerogels.
[0003] At present, aramid nanofibers obtained by deprotonation are the mainstream solution for preparing aramid nanofiber-based aerogels. The products have excellent mechanical properties and chemical stability, and the pore structure, density and performance of the aerogels can be adjusted by adjusting the preparation conditions to meet different application requirements. However, the preparation process is long, the yield is low, and a large amount of organic solvents and strong alkali are used, which cannot meet the requirements of large-scale green preparation.
[0004] In addition to the deprotonation method, aramid nanofibers can also be obtained by spinning, deprotonation, mechanical cracking, vapor deposition, phase inversion, etc., wherein the mechanical cracking method can realize the mass production of aramid nanofibers. The aramid nanofibers prepared by high-pressure homogenization and alkali treatment cracking in the patent (CN115029920B) not only retain the chemical structure and thermal stability of macroscopic aramid fibers, but also can be stably dispersed in water for a long time, realizing the large-scale green preparation of aramid nanofibers. However, the aramid nanofibers obtained by the mechanical cracking method are difficult to disperse, agglomerate seriously, and have fewer surface functional groups, and are often difficult to be directly processed into aerogels by freeze casting.
[0005] How to construct strong, multifunctional aerogels based on aramid nanofibers in a green and environmentally friendly water system is a significant challenge for the large-scale preparation of aramid nanofibers. Summary of the invention
[0006] The main purpose of the present invention is to provide a polyvinyl alcohol-assisted aramid nanofiber aerogel and its preparation method and application. The technology introduces polyvinyl alcohol into the aramid nanofiber aqueous dispersion. On the one hand, the long polymer chain is interspersed between the nanofibers to reduce fiber aggregation. On the other hand, the hydroxyl groups on the molecular chain form hydrogen bonds with the amino and carboxyl functional groups on the surface of the aramid nanofibers to further fix the fibers, so that the configuration is maintained during the freezing process, thereby obtaining an aerogel with a complete configuration after freeze drying. Since polyvinyl alcohol is easy to absorb water and regain moisture, the freeze-dried aerogel will cause fiber adhesion after compression and cannot rebound. Therefore, the aerogel is heat-treated above the decomposition temperature of polyvinyl alcohol to convert polyvinyl alcohol into a polymer containing conjugated double bonds to reduce its adhesion. The polyvinyl alcohol-assisted aramid nanofiber aerogel thus obtained can be twisted, bent, and cut, and has certain tensile recovery and compression rebound properties.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0008] (1) beating, homogenizing and centrifuging aramid pulp to obtain an aramid nanofiber aqueous dispersion;
[0009] (2) dissolving polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol aqueous solution;
[0010] (3) The aramid nanofiber aqueous dispersion and the polyvinyl alcohol aqueous solution are mixed and placed in a container, and subjected to unidirectional freezing with liquid nitrogen, freeze drying, and low-temperature heat treatment to obtain the aerogel.
[0011] Preferably, the length of the aramid pulp in step (1) is 1-10 mm; the number of revolutions of the beating is 8000-50000 rpm, and the mass concentration of the pulp obtained by beating is 1-20 wt%.
[0012] More preferably, the length of the aramid pulp is 1-5 mm; the beating speed is 10000-30000 rpm, and the mass concentration of the obtained pulp is 5-15wt%.
[0013] Preferably, the homogenization pressure is 40-120 MPa, the number of cycles is 50-150 times, and the mass concentration of the aramid nanofiber aqueous dispersion obtained by homogenization is 0.3-0.8 wt %.
[0014] More preferably, the homogenization pressure is 60-100 MPa, the number of cycles is 60-100 times, and the mass concentration of the obtained dispersion is 0.4-0.7 wt %.
[0015] Preferably, the centrifugal speed is 1000-12000 rpm, the centrifugal time is 5-60 min, and the mass concentration of the aramid nanofiber aqueous dispersion obtained by centrifugation is 0.5-2.5 wt %.
[0016] More preferably, the centrifugal speed is 5000-10000 rpm, the centrifugal time is 15-30 min, and the mass concentration of the obtained dispersion is 1-2 wt %.
[0017] Preferably, the diameter of the aramid nanofibers obtained by the preparation method is 20-500 nm.
[0018] More preferably, the aramid nanofiber has a diameter of 50-100 nm.
[0019] Preferably, the number average molecular weight of the polyvinyl alcohol in step (2) is 20,000-150,000, and the alcoholysis degree is ≥99%.
[0020] More preferably, the number average molecular weight of the polyvinyl alcohol is 50,000-100,000, and the alcoholysis degree is ≥99%.
[0021] Preferably, the dissolution temperature is 60-110° C., and the dissolution time is 0.5-5 h.
[0022] More preferably, the dissolution temperature is 80-90°C and the dissolution time is 1-3h.
[0023] Preferably, the concentration of the polyvinyl alcohol aqueous solution is 0.05-10 wt %.
[0024] More preferably, the concentration of the polyvinyl alcohol aqueous solution is 0.5-5 wt %.
[0025] Preferably, the mass ratio of the aramid nanofibers to polyvinyl alcohol in step (3) is (1:1-99:1).
[0026] More preferably, the mass ratio of aramid nanofibers to polyvinyl alcohol is (9:1-95:5).
[0027] Preferably, the mass concentration of the composite dispersion is 0.5-1.5wt%.
[0028] More preferably, the mass concentration of the composite dispersion is 0.8-1.2 wt %.
[0029] Preferably, the insulation time of the liquid nitrogen one-way freezing is 5-30 minutes.
[0030] Preferably, the freeze-drying temperature is no higher than -40°C, the pressure is no higher than 20Pa, and the drying time is 48-72h.
[0031] Preferably, the low temperature heat treatment gas atmosphere is nitrogen and / or argon.
[0032] Preferably, the low temperature heat treatment procedure is: heating to 200-500°C at a rate of 2-20°C / min at room temperature and keeping the temperature for 1-5h.
[0033] More preferably, the heating rate is 3-10°C / min, the temperature is 250-350°C, and the holding time is 1-2h.
[0034] The embodiment of the present invention provides an aramid nanofiber aerogel assisted by polyvinyl alcohol obtained by the above-mentioned preparation method, wherein the aramid nanofiber aerogel assisted by polyvinyl alcohol comprises aramid nanofibers as a supporting framework and a three-dimensional porous network structure of a polymer containing conjugated double bonds derived from polyvinyl alcohol as a cross-linking node. In addition, the embodiment also provides the use of the aerogel as an absorbing material after high-temperature carbonization. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1a is a comparison of the compression performance of the aerogel blocks prepared in Example 1 of the present invention and Comparative Example 1, and the inset is an optical photograph of the rebound of the aerogel block after compression;
[0036] Figure 1b is a SEM image of the aerogel block prepared in Example 1 of the present invention;
[0037] Figure 1c is a SEM image of the aerogel block prepared in Comparative Example 1 of the present invention;
[0038] Figure 2 It is a comparison of the tensile properties of the aerogel sheets prepared in Example 2 of the present invention and Comparative Example 2, and the inset is an optical photograph of the aerogel sheet.
[0039] Figure 3-5 This is a graph showing the relationship between the reflection loss of the carbon aerogel obtained in Examples 3-5 of the present invention and the microwave frequency and the thickness of the absorbing material.
[0040] Figure 6 It is a schematic diagram of the macroscopic morphology and microscopic structure of the aramid nanofiber aerogel assisted by polyvinyl alcohol in the present invention. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0042] Example 1
[0043] The preparation of polyvinyl alcohol-assisted aramid nanofiber aerogel block (Aerogel block) comprises the following steps:
[0044] (1) treating aramid pulp by beating, homogenizing, and centrifuging to obtain an aramid nanofiber aqueous dispersion having a mass concentration of 1.6 wt %;
[0045] (2) taking 12.50 g of the aramid nanofiber aqueous dispersion in step (1) and placing it in a beaker, adding 3.01 g of a 0.5 wt % polyvinyl alcohol aqueous solution, adding 4.49 g of deionized water, stirring with a high-speed homogenizer for 5 min and then using an ultrasonic crusher for 1 min to obtain an aramid nanofiber / polyvinyl alcohol aqueous dispersion with a mass concentration of 1.0 wt %;
[0046] (3) placing the aramid nanofiber / polyvinyl alcohol aqueous dispersion obtained in step (2) in a square silica gel mold, placing the silica gel mold on a copper table, placing the copper table in a liquid nitrogen bath, placing the solidified product obtained by unidirectional freezing with liquid nitrogen in a freeze dryer, and drying at 15 Pa, -45 ° C for 48 h to obtain a polyvinyl alcohol-assisted aramid nanofiber aerogel block;
[0047] (4) The polyvinyl alcohol-assisted aramid nanofiber aerogel block obtained in step (3) is placed in a tubular furnace for low-temperature heat treatment, the temperature is increased from room temperature to 300°C at a rate of 5°C / min and kept at 300°C for 1 hour, and finally the temperature is reduced to room temperature at a rate of 5°C / min to obtain a low-temperature heat-treated polyvinyl alcohol-assisted aramid nanofiber aerogel block, recorded as ANF / PVAAb-300°C.
[0048] The compression performance of the polyvinyl alcohol-assisted aramid nanofiber aerogel block prepared in this example is shown in Figure 1a , optical photos see Figure 1a Inset, scanning electron microscope microstructure Figure 1b .
[0049] Example 2
[0050] The preparation of polyvinyl alcohol-assisted aramid nanofiber aerogel tablet comprises the following steps:
[0051] (1) treating aramid pulp by beating, homogenizing, and centrifuging to obtain an aramid nanofiber aqueous dispersion having a mass concentration of 1.6 wt %;
[0052] (2) taking 12.50 g of the aramid nanofiber aqueous dispersion in step (1) and placing it in a beaker, adding 3.01 g of a 0.5 wt % polyvinyl alcohol aqueous solution, adding 4.49 g of deionized water, stirring with a high-speed homogenizer for 5 min and then using an ultrasonic crusher for 1 min to obtain an aramid nanofiber / polyvinyl alcohol aqueous dispersion with a mass concentration of 1.0 wt %;
[0053] (3) Spreading the aramid nanofiber / polyvinyl alcohol aqueous dispersion obtained in step (2) in a circular silica gel mold, placing the silica gel mold on a copper table, placing the copper table in a liquid nitrogen bath, placing the solidified product obtained by unidirectional freezing of liquid nitrogen in a freeze dryer, and drying at 15 Pa, -45 ° C for 48 h to obtain a polyvinyl alcohol-assisted aramid nanofiber aerogel sheet;
[0054] (4) The polyvinyl alcohol-assisted aramid nanofiber aerogel sheet obtained in step (3) is placed in a tubular furnace for low-temperature heat treatment, the temperature is increased from room temperature to 300°C at a rate of 5°C / min and kept at 300°C for 1 hour, and finally the temperature is decreased to room temperature at a rate of 5°C / min to obtain a low-temperature heat-treated polyvinyl alcohol-assisted aramid nanofiber aerogel sheet, recorded as ANF / PVAAt-300°C.
[0055] The tensile properties of the polyvinyl alcohol-assisted aramid nanofiber aerogel sheet prepared in this embodiment are shown in FIG. Figure 2 , optical photos see Figure 2 illustration.
[0056] In order to prove that the introduction of polyvinyl alcohol is beneficial to the improvement of the configuration and mechanical properties of aramid nanofibers, pure aramid nanofiber aerogel blocks and aerogel sheets were prepared as comparative examples 1-2:
[0057] Comparative Example 1
[0058] The preparation of pure aramid nanofiber aerogel block (Aerogel block) includes the following steps:
[0059] (1) treating aramid pulp by beating, homogenizing, and centrifuging to obtain an aramid nanofiber aqueous dispersion having a mass concentration of 1.6 wt %;
[0060] (2) 12.50 g of the aramid nanofiber aqueous dispersion in step (1) was placed in a beaker, 7.5 g of deionized water was added, and the mixture was stirred for 5 min using a high-speed homogenizer and then ultrasonicated for 1 min using an ultrasonic crusher to obtain an aramid nanofiber aqueous dispersion with a mass concentration of 1.0 wt%;
[0061] (3) placing the aramid nanofiber aqueous dispersion obtained in step (2) in a square silica gel mold, placing the silica gel mold on a copper table, placing the copper table in a liquid nitrogen bath, placing the solidified product obtained by unidirectional freezing of liquid nitrogen in a freeze dryer, and drying at 15 Pa, -45 ° C for 48 h to obtain an aramid nanofiber aerogel block;
[0062] (4) The aramid nanofiber aerogel block obtained in step (3) is placed in a tubular furnace for low-temperature heat treatment, the temperature is increased from room temperature to 300°C at a rate of 5°C / min and kept at 300°C for 1 h, and finally the temperature is decreased to room temperature at a rate of 5°C / min to obtain a low-temperature heat-treated aramid nanofiber aerogel block, recorded as ANFAb-300°C.
[0063] The compression performance of the aramid nanofiber aerogel prepared in this comparative example is shown in Figure 1a , optical photos see Figure 1a Illustration, scanning electron microscope microstructure Figure 1c .
[0064] Comparative Example 2
[0065] The preparation of pure aramid nanofiber aerogel tablet includes the following steps:
[0066] (1) treating aramid pulp by beating, homogenizing, and centrifuging to obtain an aramid nanofiber aqueous dispersion having a mass concentration of 1.6 wt %;
[0067] (2) 12.50 g of the aramid nanofiber aqueous dispersion in step (1) was placed in a beaker, 7.5 g of deionized water was added, and the mixture was stirred for 5 min using a high-speed homogenizer and then ultrasonicated for 1 min using an ultrasonic crusher to obtain an aramid nanofiber aqueous dispersion with a mass concentration of 1.0 wt%;
[0068] (3) spreading the aramid nanofiber aqueous dispersion obtained in step (2) in a circular silica gel mold, placing the silica gel mold on a copper table, placing the copper table in a liquid nitrogen bath, placing the solidified product obtained by unidirectional freezing of liquid nitrogen in a freeze dryer, and drying at 15 Pa, -45 ° C for 48 h to obtain an aramid nanofiber aerogel sheet;
[0069] (4) The aramid nanofiber aerogel sheet obtained in step (3) is placed in a tubular furnace for low-temperature heat treatment, the temperature is increased from room temperature to 300°C at a rate of 5°C / min and kept at 300°C for 1 h, and finally the temperature is decreased to room temperature at a rate of 5°C / min to obtain a low-temperature heat-treated aramid nanofiber aerogel sheet, which is recorded as ANFAt-300°C.
[0070] The tensile properties of the aramid nanofiber aerogel sheet prepared in this comparative example are shown in Figure 2 , optical photos see Figure 2 illustration.
[0071] Example 3
[0072] The preparation of microwave absorbing carbon aerogel derived from polyvinyl alcohol-assisted aramid nanofiber aerogel blocks carbonized at 700°C comprises the following steps:
[0073] (1) treating aramid pulp by beating, homogenizing, and centrifuging to obtain an aramid nanofiber aqueous dispersion having a mass concentration of 1.6 wt %;
[0074] (2) taking 12.50 g of the aramid nanofiber aqueous dispersion in step (1) and placing it in a beaker, adding 3.01 g of a 0.5 wt % polyvinyl alcohol aqueous solution, adding 4.49 g of deionized water, stirring with a high-speed homogenizer for 5 min and then using an ultrasonic crusher for 1 min to obtain an aramid nanofiber / polyvinyl alcohol aqueous dispersion with a mass concentration of 1.0 wt %;
[0075] (3) placing the aramid nanofiber / polyvinyl alcohol aqueous dispersion obtained in step (2) in a square silica gel mold, placing the silica gel mold on a copper table, placing the copper table in a liquid nitrogen bath, placing the solidified product obtained by unidirectional freezing with liquid nitrogen in a freeze dryer, and drying at 15 Pa, -45 ° C for 48 h to obtain a polyvinyl alcohol-assisted aramid nanofiber aerogel block;
[0076] (4) The polyvinyl alcohol-assisted aramid nanofiber aerogel block obtained in step (3) is placed in a tubular furnace for high-temperature carbonization, the temperature is increased from room temperature to 500°C at a rate of 5°C / min and kept at 500°C for 1 h, the temperature is increased from 500 to 700°C at a rate of 5°C / min and kept at 700°C for 1 h, and finally the temperature is cooled at a rate of 5°C / min to obtain a carbon aerogel derived from the polyvinyl alcohol-assisted aramid nanofiber aerogel block by high-temperature carbonization, which is recorded as ANF / PVAAb-700°C.
[0077] Example 4
[0078] The preparation of microwave absorbing carbon aerogel derived from aramid nanofiber aerogel blocks assisted by polyvinyl alcohol and carbonized at 800°C comprises the following steps:
[0079] (1) treating aramid pulp by beating, homogenizing, and centrifuging to obtain an aramid nanofiber aqueous dispersion having a mass concentration of 1.6 wt %;
[0080] (2) taking 12.50 g of the aramid nanofiber aqueous dispersion in step (1) and placing it in a beaker, adding 3.01 g of a 0.5 wt % polyvinyl alcohol aqueous solution, adding 4.49 g of deionized water, stirring with a high-speed homogenizer for 5 min and then using an ultrasonic crusher for 1 min to obtain an aramid nanofiber / polyvinyl alcohol aqueous dispersion with a mass concentration of 1.0 wt %;
[0081] (3) placing the aramid nanofiber / polyvinyl alcohol aqueous dispersion obtained in step (2) in a square silica gel mold, placing the silica gel mold on a copper table, placing the copper table in a liquid nitrogen bath, placing the solidified product obtained by unidirectional freezing with liquid nitrogen in a freeze dryer, and drying at 15 Pa, -45 ° C for 48 h to obtain a polyvinyl alcohol-assisted aramid nanofiber aerogel block;
[0082] (4) The polyvinyl alcohol-assisted aramid nanofiber aerogel block obtained in step (3) is placed in a tubular furnace for high-temperature carbonization, the temperature is increased from room temperature to 500°C at a rate of 5°C / min and kept at 500°C for 1 h, the temperature is increased from 500 to 800°C at a rate of 5°C / min and kept at 800°C for 1 h, and finally the temperature is cooled at a rate of 5°C / min to obtain a carbon aerogel derived from the polyvinyl alcohol-assisted aramid nanofiber aerogel block by high-temperature carbonization, which is recorded as ANF / PVAAb-800°C.
[0083] Example 5
[0084] The preparation of microwave absorbing carbon aerogel derived from polyvinyl alcohol-assisted aramid nanofiber aerogel blocks carbonized at 900°C comprises the following steps:
[0085] (1) treating aramid pulp by beating, homogenizing, and centrifuging to obtain an aramid nanofiber aqueous dispersion having a mass concentration of 1.6 wt %;
[0086] (2) taking 12.50 g of the aramid nanofiber aqueous dispersion in step (1) and placing it in a beaker, adding 3.01 g of a 0.5 wt % polyvinyl alcohol aqueous solution, adding 4.49 g of deionized water, stirring with a high-speed homogenizer for 5 min and then using an ultrasonic crusher for 1 min to obtain an aramid nanofiber / polyvinyl alcohol aqueous dispersion with a mass concentration of 1.0 wt %;
[0087] (3) placing the aramid nanofiber / polyvinyl alcohol aqueous dispersion obtained in step (2) in a square silica gel mold, placing the silica gel mold on a copper table, placing the copper table in a liquid nitrogen bath, placing the solidified product obtained by unidirectional freezing with liquid nitrogen in a freeze dryer, and drying at 15 Pa, -45 ° C for 48 h to obtain a polyvinyl alcohol-assisted aramid nanofiber aerogel block;
[0088] (4) The polyvinyl alcohol-assisted aramid nanofiber aerogel block obtained in step (3) is placed in a tubular furnace for high-temperature carbonization, the temperature is increased from room temperature to 500°C at a rate of 5°C / min and kept at 500°C for 1 h, the temperature is increased from 500 to 900°C at a rate of 5°C / min and kept at 900°C for 1 h, and finally the temperature is cooled at a rate of 5°C / min to obtain a carbon aerogel derived from the polyvinyl alcohol-assisted aramid nanofiber aerogel block by high-temperature carbonization, which is recorded as ANF / PVAAb-900°C.
[0089] Performance Testing:
[0090] The carbon aerogel obtained in Examples 3-5 was paraffin-impregnated, cut and punched to form a coaxial ring, and the real and imaginary parts of the dielectric constant and the real and imaginary parts of the magnetic permeability of the sample at 1-18 GHz were tested using the coaxial test method of the Agilent E5071C microwave network vector analyzer in the United States. Finally, the microwave absorption performance of the material was calculated based on the electromagnetic parameters. The results are as follows:
[0091] Figure 3-5 This is the relationship between the reflection loss of carbon aerogel and the microwave frequency and the thickness of the absorbing material:
[0092] Figure 3 When the carbonization temperature is 700℃, the reflection loss value of the sample at 8mm can reach -27.348dB, and an effective absorption bandwidth of 6.04GHz can be obtained at the same thickness.
[0093] Figure 4 When the carbonization temperature is 800℃, the reflection loss value of the sample at 2.7mm can reach -67.296dB, and an effective absorption bandwidth of 7.12GHz can be obtained at a thickness of 3.0mm.
[0094] Figure 5 When the carbonization temperature is 900℃, the reflection loss value of the sample at 2.3mm can reach -27.921dB, and an effective absorption bandwidth of 7.69GHz can be obtained at a thickness of 3.0mm.
[0095] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A method for preparing polyvinyl alcohol-assisted aramid nanofiber aerogel, characterized in that: include: The aramid pulp is subjected to beating, homogenizing and centrifugal operations to obtain an aramid nanofiber aqueous dispersion; dissolving polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol aqueous solution; The aramid nanofiber aqueous dispersion and the polyvinyl alcohol aqueous solution are mixed and placed in a container, and subjected to unidirectional freezing with liquid nitrogen, freeze drying, and low-temperature heat treatment to obtain the aerogel.
2. The preparation method according to claim 1, characterized in that: During the preparation process of the aramid nanofiber aqueous dispersion, the length of the aramid pulp is 1-10mm; the number of revolutions of the pulping is 8000-50000rpm, and the mass concentration of the pulp obtained by pulping is 1-20wt%; the pressure of the homogenization is 40-120MPa, the number of cycles is 50-150 times, and the mass concentration of the aramid nanofiber aqueous dispersion obtained by homogenization is 0.3-0.8wt%; the centrifugal speed is 1000-12000rpm, the centrifugal time is 5-60min, and the mass concentration of the aramid nanofiber aqueous dispersion obtained by centrifugation is 0.5-2.5wt%; the diameter of the aramid nanofiber obtained by the preparation method is 20-500nm.
3. The preparation method according to claim 1, characterized in that: The number average molecular weight of the polyvinyl alcohol is 20000-150000, and the alcoholysis degree is ≥99%; the dissolution temperature is 60-110° C., and the dissolution time is 0.5-5h; and the concentration of the polyvinyl alcohol aqueous solution is 0.05-10wt%.
4. The preparation method according to claim 1, characterized in that: When the aramid nanofiber aqueous dispersion is mixed with the polyvinyl alcohol aqueous solution, the mass ratio of the aramid nanofiber to the polyvinyl alcohol is (1:1-99:1), and the mass concentration of the obtained composite dispersion is 0.5-1.5wt%.
5. The preparation method according to claim 1, characterized in that: The holding time of the liquid nitrogen unidirectional freezing is 5-30min; The freeze-drying temperature is no higher than -40°C, the pressure is no higher than 20Pa, and the drying time is 48-72h.
6. The preparation method according to claim 1, characterized in that: The low temperature heat treatment gas atmosphere is nitrogen and / or argon; the low temperature heat treatment procedure is: heating to 200-500°C at a rate of 2-20°C / min at room temperature and keeping the temperature for 1-5h.
7. Aramid nanofiber aerogel obtained by the preparation method according to any one of claims 1 to 6 with the assistance of polyvinyl alcohol.
8. Application of the derived carbon aerogel obtained by high-temperature carbonization of the aerogel according to claim 7 in the field of microwave absorption.
9. The use according to claim 8, characterized in that: The high-temperature carbonization gas atmosphere is nitrogen and / or argon; the high-temperature carbonization procedure is: heating to 500°C at a rate of 2-20°C / min at room temperature, and keeping at 500°C for 1-2h, then heating to 700°C / 800°C / 900°C at a rate of 2-20°C / min and keeping for 1-2h.
Citation Information
Patent Citations
A method for preparing aramid nanofiber
CN115029920B
Aramid nanofiber-based composite aerogel and preparation method thereof
CN113278191A
Preparation method of nanocellulose / aramid nanofiber carbon aerogel with super-elasticity, ultralight and high compressibility, carbon aerogel and application
CN114956036A
Carbon nanofiber aerogel microsphere and preparation method thereof
CN115159500A
Aramid-assisted polyvinyl alcohol aerogel as well as preparation method and application thereof
CN115368625A
Cited By
High-concentration aramid nanofiber dispersion liquid as well as preparation method and application thereof
CN121574389A
High-concentration aramid nanofiber dispersion liquid, preparation method and application thereof
CN121574389B
Preparation method of hyperelastic porous carbon aerogel for VC vapor chamber test, carbon aerogel and application
CN122212755A